Macro and Micronutrients of 44 Medicinal Plant Species Used Traditionally in Nuevo Leon, Mexico - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Degu, Hewan Demissie; Kumari, Ch. Aruna; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2016)
An analysis of macro and micronutrients among 44 species of medicinal plants utilized traditionally to control diabetes and other diseases in Nuevo Leon, Mexico carried out at the experimental station of Facultad de Ciencias Forestales, Universidad Autonoma de Nuevo Leon, located in the municipality of Linares showed a large variability in the contents of macro and micronutrients and protein. K exhibited a wide range of variability among the selected medicinal plants 5.47−163.35 (mg g-1 dw), Mg from 0.1−8.64 (mg g-1 dw), P varied from 0.18−5.79 (mg g-1 dw), C from 25.54−51.66%, N from 1.36−6.25%, C/N from 5.34−31.05% and with respect to micronutrients Cu ranged from 4.17−33.88 (µg g-1 dw), Fe from 98.28−3977.55 (µg g-1 dw), Zn from 9.49−266.31 (µg g-1 dw). It is assessed that some species contain high amount of nutrients (macro and micronutrients thereby confirming their efficacy to combat various diseases and provide an opportunity to scientists working on medicinal plants to select the species with high nutrient contents.